Use of Chitosan and Chitosan–Magnetite Spheres for Arsenic Groundwater Removal: Factorial Designs as Tools to Optimize the Efficiency of Removal - Mayra Hernández Trespalacios; María Florencia Mangiameli; Lina Gribaudo; María Inés Frascaroli; Juan Carlos González (Inorganics)
The lack of access to drinking water is a problem affecting many regions worldwide. In Santa Fe, Argentina, the population uses groundwater as a source of drinking water. Unfortunately, it has high concentrations of As(V), which makes it unsuitable for consumption. Despite several methods for As(V) quantification and elimination, the high cost and technical difficulties in their implementation make many of them cost-ineffective, especially in small communities. In this work, a hybrid sorbent of magnetite–chitosan spheres (M-Q) is synthesized, and its sorption capacity is evaluated by employing groundwater with high conductivity (12.1 mS/cm) and hardness (1125 mg/L CaCO3) and an As(V) concentration of 0.265 mg/L. A colorimetric analytical technique, which is sufficiently sensitive, simple, and economical to apply, is used for As(V) quantification. The experimental results indicate that the sorption capacity for As(V) removal is 80.1% (sorbent mass 0.466 g, time 85.3 min, and pH 5.9), with the advantage of the capability of being independent of its magnetic properties. The optimal experimental conditions for As(V) sorption (pH, time, and mass of the hybrid sorbent M-Q) are obtained by response surface factorial designs, which significantly reduce the total number of experiments and, at the same time, demonstrate that all the selected variables significantly affect the As(V) sorption percentage (response studied).